A Study on Bead-on-Plate Welding of AA7075 using Low Power Fiber Laser - Muhammad Naqiuddin, Mat Salleh; M., Ishak; F. R. M., Romlay; Aiman, Mohd Halil (Faculty Mechanical Engineering, UMP, 2016)
Laser welding promises the best method to produce higher strength of aluminium joints compared to conventional arc welding process. Arc welding usually produces a large heat affected zone (HAZ), which leads to lower joint strength on aluminium alloys. AA7075 aluminium alloy has many advantages due to its light weight, low density, high corrosion resistance, and high alloy strength as compared to steel. This paper presents a weld feasibility studies on AA7075 surface using low power fiber laser with two different modes; continuous wave (CW) and pulse wave (PW) modes. The intention of this research work is to investigate the effect of laser welding modes with different focal position on penetration depth, type of weld penetration, and microstructure of bead on plate welded AA 7075 using low power fiber laser. The bead-on-plate (BOP) welding was carried out by heating the surface of AA7075 with a thickness of 2 mm using both CW and PW modes with focal lengths that ranged from 60 to 200 mm. 90 % power was used for both welding modes with the same welding speed, 2 mm/s. The macrostructure of the welded line was captured using an optical microscope, and the beam width and penetration were measured. The smallest bead was observed at 120 mm focal length with 570 µm diameter. Pulse wave (PW) welding with keyhole profile produced optimum penetration depth, which was approximately 1.0 mm. However, continuous mode (CW) welding produced 0.153 mm penetration depth. To conclude, AA 7075 could be joined using the low power fiber laser welding method since the half weld penetration with keyhole profile was produced. For better welding joint with fewer defects, shielding gas and incident angle of laser beam could be applied